Metacognition in Cognitive and Learning Sciences: Psychological Approaches to Self-Regulated Learning - Omar Mustadiri; Farahana Natasya (PT Mutiara Bustan Ilmu, 2025)
This study explores the role of metacognition in the field of cognitive and learning sciences with a particular emphasis on psychological approaches to self-regulated learning. Metacognition, defined as the ability to reflect on and control one’s own cognitive processes, plays a crucial role in students’ ability to plan, monitor, and evaluate their learning strategies. The research employs a mixed-method approach, combining quantitative data from learning performance assessments with qualitative insights from interviews and reflective journals. Findings reveal that learners who engage in metacognitive practices demonstrate greater autonomy, improved problem-solving skills, and stronger academic achievement. Furthermore, psychological theories of self-regulation provide a valuable framework for understanding how metacognition supports motivation, goal-setting, and resilience in learning contexts. This study contributes to bridging the gap between cognitive science, psychology, and educational practice by highlighting the importance of fostering metacognitive skills in both formal and informal learning environments.